THE STRATEGY OF PRIORITY LOCATION (LOKPRI) IN STATE BORDER DEVELOPMENT BASED ON MASTER PLAN OF STATE BORDER MANAGEMENT - Johnson Kennedy, Posma Sariguna; L.Tobing, Suzanna Josephine; Bastian Heatubun, Adolf; Lumbantoruan, Rutman; Tampubolon, Emma (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Many government policies at the micro level of the region have not been able to be realized. Need to answer the various needs of the development of border areas that have been very urgent from various strategic problems that exist. This paper is to view border area management in Priority Sites. The methodology undertaken is by conducting normative studies, in which strategic issues of Priority Locations (Lokpri) are obtained through literature studies. The purpose of establishing Lokpri's policy review strategy is to produce a border area development plan that can be a common reference for all stakeholders.Keywords: Priority Location (Lokpri), State Border Area, Spatial Plan (RTRW)